Use of traditional medicines and traditional practitioners by children in Indonesia: findings from a national population survey in 2014–2015 - Pengpid, Supa (J Multidiscip Healthc, 2019)
Background: Little data are available about traditional and complementary medicine use in children in the general population in Southeast Asia, including Indonesia. The aim of this investigation was to assess the prevalence of the use of traditional medicines and traditional practitioners in children in a national population-based survey in Indonesia. Methods: The cross-sectional sample included 15,739 children (0–14 years) (median age 7.0 years, inter quartile range =7.0) that took part in the Indonesia Family Life Survey in 2014–2015. Results: The prevalence of use of traditional medicines as a treatment in the past four weeks was 6.2%, vitamins or supplements 19.9%, and over-the-counter modern medicine 61.1%. The prevalence of traditional practitioner use in the past 4 weeks was 3.4%, and the prevalence of the use of traditional medicines and/or traditional practitioner in the past 4 weeks was 8.8%. The purpose of consulting the traditional practitioner was mainly massage (86.8%) and treatment for illness (14.8%). In the adjusted logistic regression analysis, having a birth certificate (as a proxy for better economic status) and poor self-rated health were associated with traditional medicine use. Younger age and poor self-rated health were associated with traditional practitioners use. Conclusion: A high prevalence of traditional medicine use in children in Indonesia was found, and several social factors and poor health status of its use were identified.